2022
DOI: 10.1016/j.vaccine.2022.01.040
|View full text |Cite
|
Sign up to set email alerts
|

B-cell cytopenia and time to last B-cell-depleting therapy predict response to SARS-COV-2 vaccines in patients with lymphoproliferative disorders

Abstract: Patients with B-non-Hodgkin lymphoma (NHL) are at increased risk of morbidity and mortality from SARS-CoV-2. We investigated the relationship between B cell cytopenia and the SARS-CoV-2 vaccine response in B-NHL patients. We measured anti-RBD antibodies and the lymphocyte immunophenotype in 19 controls, 22 lymphoma patients on observation (cohort 1) and 55 lymphoma patients receiving their vaccines post B-cell depleting therapy (cohort 2). Half of the lymphoma patients in both cohorts achieved seropositivity c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
(22 reference statements)
2
7
0
Order By: Relevance
“…The other important point of our study is the insufficient antibody production in patients with BCL who received vaccination before the initiation of anti-CD20 MoAb treatment. Although this result was concordant with the result reported by Tanguay, 15 this was, at the same time, discordant with the findings of a previous study that reported that nAb remained for 4 months after vaccination in patients subsequently treated with B-cell depletion therapy. 9 The underlying reason for this discrepancy is currently unclear, although our study and the study by Tanguay et al included only 15 and 22 patients, respectively.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The other important point of our study is the insufficient antibody production in patients with BCL who received vaccination before the initiation of anti-CD20 MoAb treatment. Although this result was concordant with the result reported by Tanguay, 15 this was, at the same time, discordant with the findings of a previous study that reported that nAb remained for 4 months after vaccination in patients subsequently treated with B-cell depletion therapy. 9 The underlying reason for this discrepancy is currently unclear, although our study and the study by Tanguay et al included only 15 and 22 patients, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, there is consensus regarding the importance of the duration from completion of B-cell depletion therapy to vaccination within 6 to 12 months, which significantly impairs nAb production against the SARS-Cov-2 RNA vaccine. 10 , 12 , 13 , 15 In this regard, although data about the precise lymphocyte subset were unfortunately unavailable in our cohort, our study may preclude the necessity of precise blood cell/lymphocyte profiling, which is both labor-intensive and sometimes expensive, for predicting prompt nAb production after COVID-19 vaccination in a specific population of patients with BCL who were previously treated with B-cell depletion therapy.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Other strategies to improve seroconversion may be the choice of an alternative treatment if available (i.e. TPO-RA versus rituximab in ITP), vaccinating before B-cell depleting drugs, and allowing enough time for immune reconstitution in patients treated with B-cell depleting agents, as already suggested for lymphoproliferative disorders 20 , 21 . In this regard, Tanguay et al showed that rates of seroconversion raised to 88% if lymphoma patients had received B-cell depletion > 2 years prior to vaccine (versus 5% in those treated within 1 year before vaccine) 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, there is major concern about the efficacy of COVID-19 vaccines in individuals treated with B-cell-depleting immunotherapy, as the experience with other vaccines has shown an impaired humoral response [ 1 , 2 , 3 ]. Recent studies confirmed that seroconversion in individuals on treatment with anti-CD20 after receiving two doses against COVID-19 is suboptimal compared with healthy donors (<10%) [ 45 , 46 ]. This percentage significantly increases after ceasing the treatment, from 17.5% in patients that ended anti-CD20 less than 6 months earlier [ 47 ] to higher results of 66–80% [ 28 , 45 , 47 , 48 ] 6–9 months since the last dose, which also concurs with the time of peripheral B-cell aplasia recovery.…”
Section: Discussionmentioning
confidence: 99%